2013
DOI: 10.1111/1440-1630.12096
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of excellence in practice educators: The perspectives of Australian occupational therapy students

Abstract: Aim: Occupational therapists frequently undertake the role of practice educator contributing to the development of the future workforce, however, little is known about how they effectively perform this role. This study aimed to elucidate students' perspectives on what makes an excellent practice educator. Method: Documentation for 124 Practice Excellence Commendations nominations by Queensland occupational therapy students for Queensland Occupational Therapy Fieldwork Collaborative awards between 2008 and 2011… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 15 publications
6
51
0
5
Order By: Relevance
“…Findings from the present study suggest that supervisors identified positive and important practice experiences similar to student responses in the literature. Positive characteristics for both fieldwork supervisors and students included self-directed learning, hands-on training, interdisciplinary communication, and exposure to a variety of cases and clients, which align with the literature based on student responses (Rodger et al, 2014;Towns & Ashby, 2014). In addition, 95% of the survey respondents in the present study feel responsible for adapting to a student's learning style, a characteristic students value more than any other educator behavior (Koski et al, 2013).…”
Section: Suggestions On How Fieldwork Can Be Improvedsupporting
confidence: 80%
See 1 more Smart Citation
“…Findings from the present study suggest that supervisors identified positive and important practice experiences similar to student responses in the literature. Positive characteristics for both fieldwork supervisors and students included self-directed learning, hands-on training, interdisciplinary communication, and exposure to a variety of cases and clients, which align with the literature based on student responses (Rodger et al, 2014;Towns & Ashby, 2014). In addition, 95% of the survey respondents in the present study feel responsible for adapting to a student's learning style, a characteristic students value more than any other educator behavior (Koski et al, 2013).…”
Section: Suggestions On How Fieldwork Can Be Improvedsupporting
confidence: 80%
“…Understanding a student's learning style, grading student exposure to more challenging areas of practice, encouraging self-directed learning, and providing balanced and timely feedback are consistent indicators of quality supervision and significantly influence student learning (Koski, Simon, & Dooley, 2013;Rodger et al, 2014;Towns & Ashby, 2014). Difficulty articulating professional reasoning from theory to practice is reported among occupational therapists in the literature (Kinn & Aas, 2009) and may contribute to a perception by students that a disconnect exists between the classroom and practice (Elliot, Velde, & Wittman, 2002;Towns & Ashby, 2014).…”
mentioning
confidence: 99%
“…Em nossa pesquisa obtivemos resultados similares a outros trabalhos 4,8,10 , indicando que para exercer a função de supervisor é necessário embasamento científico; experiência no campo de atuação; habilidades didáticas; e, principalmente, domínio teórico-clínico.…”
Section: Discussionunclassified
“…Esse processo depende da construção da relação e do diálogo entre supervisor e estudante, da compreensão do estilo de aprendizagem do aluno, e da construção de uma relação "de confiança e dependência" (p.80) 1 , que promoverá a autonomia do estudante, além da oferta de suporte subjetivo e emocional, e de feedback 4,[8][9][10] . Muitos trabalhos na área abordam a questão do ensino-aprendizagem no estágio em uma tentativa de avaliação, revisão e busca de novas estratégias para melhor adequá-lo às exigências sociais 11,12 .…”
Section: Introductionunclassified
See 1 more Smart Citation